Stilbestrol in a guinea pig ration. - Wheat, J.D.; Menzies, C.S.; Holland, L.A. (Kansas Agricultural Experiment Station, 2011)
This study was to determine the response of young guinea pigs to stilbestrol added to the basic ration of ground oats, tankage, bonemeal, ground alfalfa hay, and freshly-cut, green alfalfa. Eight litters of guinea pigs, each consisting of two pigs of the same sex were used. These pigs ranged from 3 to 5 weeks of age and the initial weights ranged from 220.7 to 368.6 grams. Four of the litters were males and four were females. One male from each of the male litters was placed in the control cage and the other pig from each litter was placed in the treatment cage. The female litters were divided in a similar manner and an effort was made to equalize the initial weights in the control and treatment cages for each sex.
Keywords: Guinea pig; Stilbestrol; Ration; Gain